ENERGY EFFICIENT LOAD BALANCING FOR CLOUD DATA CENTER - Rivankar, Amey; G, Anusooya (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Cloud computing is the latest trend in large-scale distributed computing. It provides diverse services on demand to distributive resources such as servers, software, and databases. One of the challenging problems in cloud data centers is to manage the load of different reconfigurable virtual machines over one another. Thus, in the near future of cloud computing field, providing a mechanism for efficient resource management will be very significant. Many load balancing algorithms have been already implemented and executed to manage the resources efficiently and adequately. The objective of this paper is to analyze shortcomings of existing algorithms and implement a new algorithm which will give optimized load balancing result.